Winning the Global Surgery War: A Conceptual Framework - Peter M. Nthumba, MBChB, MMed(Surg), MSc(Epid) (Plastic and Reconstructive Surgery, Global Open)
Background:. Global surgery (GS), which comprises surgery, obstetrics, and anesthesia, is a complex multidisciplinary enterprise that focuses on the provision of timely, safe, and equitable surgical care to the global population. As with any war, understating the burden of surgical disease risks failure in any crafted strategy, as the measures would be substantially inadequate. Using strategies from successful large-scale interventions, the author proposes a conceptual framework for sustainable GS scale-up. Methods:. The author collated GS scale-up strategies from the literature and aligned them with the 6 core indicator metrics as the primary outcome measures. Results:. The proposed conceptual framework hangs on the successes of the Marshall Plan for Europe and the World Health Organization multimodal strategy for infection control and prevention to provide funding and intervention models, successively, for GS scale-up. Smile Train and Operation Smile strategies for strengthening surgical systems provide potential learning points for GS scalability. Collaborating with these and other surgical nongovernmental organizations and harnessing their experiences and networks promises potential for success in GS scale-up. Conclusions:. The proposed conceptual framework provides potential sustainable GS scale-up, using a nonprescriptive “bundled” intervention approach, permitting individual countries to progress at their own pace, while allowing for transparent sharing of learned experiences.